The Effect of Rebranding, Brand Image, and Marketing Strategy on Customer Satisfaction: Case Study: Ace Hardware Becomes Az.ko Living World Alam Sutera - Husaini, Ahmad Fakhri; Yetmi, Yosi Safri; Ratnasari, Aisyah (PT. Batari Edu Calya, 2025)
This study uses a quantitative approach with a survey method. There were 180 respondents consisting of ACE Hardware customers before and after the rebranding to Az.ko. To select the sample, the researcher used non-probability sampling with purposive sampling, which is selecting respondents who meet the criteria of being at least 21 years old and have made purchases from both brands. Data was collected through an online questionnaire and analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) with the assistance of SMART PLS 3 software. The analysis results indicate that rebranding and brand image do not have a significant impact on customer satisfaction. Marketing strategies were found to have a positive and significant impact on customer satisfaction. These findings suggest that effective marketing efforts following rebranding are more influential in enhancing customer satisfaction than changes to the brand or brand image itself.